Visualization of time-dependent foam simulation data. - Dan R Lipsa (2013)
Research in the field of complex fluids such as polymer solutions, particulate suspensions and foams studies how the flow of fluids with different material parameters changes as a result of various constraints. Surface Evolver, the standard solver software used to generate foam simulations, provides large, complex, time-dependent data sets with hundreds or thousands of individual bubbles and thousands of time steps. However this software has limited visualization capabilities, and no foam specific visualization software exists. We describe the foam research application area where, we believe, visualization has an important role to play. We present a novel application, called Foam Vis, that provides various techniques for visualization, exploration and analysis of foam simulation data. Foam Vis can visualize individual time steps or produce time-dependent visualizations. It can process a simulation or it can facilitate comparison of several related simulations. We show new features in foam simulation data and new insights into foam behavior discovered using our application. Based on the many research questions that domain experts are able to address, we believe we provide a valuable tool for visualization and analysis of data in the foam research community.